Simultaneous exposure of transformed cells to SRC family inhibitors and CHK1 inhibitors causes cell death - Mitchell, Clint (Landes Bioscience, 2011)
The present studies were initiated to determine in greater molecular detail the regulation of CHK1 inhibitor lethality in transfected and infected breast cancer cells and using genetic models of transformed fibrobalsts. Multiple MEK1/2 inhibitors (PD184352, AZD6244 [ARRY-142886]) interacted with multiple CHK1 inhibitors (UCN-01 [7-hydroxystaurosporine], AZD7762) to kill mammary carcinoma cells and transformed fibroblasts. In transformed cells, CHK1 inhibitor-induced activation of ERK1/2 was dependent upon activation of SRC family non-receptor tyrosine kinases as judged by use of multiple SRC kinase inhibitors (PP 2, Dasatinib; AZD0530), use of SRC/FYN/YES deleted transformed fibroblasts or by expression of dominant negative SRC. Cell killing by SRC family kinase inhibitors and CHK1 inhibitors was abolished in BAX/BAK(−/−) transformed fibroblasts and suppressed by overexpression of BCL-X(L). Treatment of cells with BCL-2/BCL-X(L) antagonists promoted SRC inhibitor + CHK1 inhibitor-induced lethality in a BAX/BAK-dependent fashion. Treatment of cells with [SRC + CHK1] inhibitors radio-sensitized tumor cells. These findings argue that multiple inhibitors of the SRC-RAS-MEK pathway interact with multiple CHK1 inhibitors to kill transformed cells.